DEKONSTRUKSI PERAN TOKOH DALAM NOVEL PESANTREN IMPIAN KARYA ASMA NADIA - Yunita Puspitasari; Ira Eko Retnosari (Buana Bastra, 2020)
"Novel" Pesantren Impian is a novel that tells the promiscuity of middle and upper class that emphasize their moral behavior. The interesting thing about this novel is to raise stories about religion and lifestyle issues, and was chosen to be featured in an adaptation to the theater performance in Iowa.The purpose of the research with the title of the Deconstruction the role of the characters in novels a Pesantren Impian of Asma Nadia. For the firsy describes some of the characters that could describe. The theory used in research the theory of deconstruction. The Derrida’s said that deconstruction can be reviewed from the aspect of characters. Therefore, the purposes of research is to know characterization and deconstruction the role of the characters novels. The approach used in this study is descriptive a qualitative. The data used in research in the form of words, sentences, and discourses related to the object of research contained in the novel Pesantren Impian works Asma Nadia. The source of data used in this research is the novel Pesantren Impian works by Asma Nadia published in January 2016, 300 pages. Data collection techniques used in this study are the techniques of reading, notes, and investigator techniques. The results of this presentation are presented in the form of descriptive exposure. Based on the results of descriptive analysis of novel Pesantren Impian of Asma Nadia's work in the following results. There are 18 characters have been described to know the existing characterizations, namely Santi, Sinta, Rini, Ita, Iin, Sisy, Inong, Evi, Butet, Ipung, Sri, Yanti, Tanti, Umar, Mas Good, Teungku Budiman, Mrs. Rini, Lik Kusno. Two antagonists or black character and sixteen protagonists or white character. While in the deconstruction role of the characters in the novel Pesantren Impian works Asma Nadia only a few figures that can be deconstructed, namely Teungku Budiman, Rini, Mas Good, Sisy, and Mr. Lik Kusno. because in general the reader assumes that the antagonist can not turn into a protagonist. However, in this deconstruction the antagonist becomes the protagonist, while the protagonist becomes an antagonist.